2003
DOI: 10.1016/s0301-472x(03)00264-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine levels and acute graft-versus-host disease after HLA-identical hematopoietic stem cell transplantation

Abstract: These results support the idea that a balance between cytokines derived from type 1 and type 2 T-helper cells may be important in the development and control of aGVHD. Although sIL-2R, TNF-alpha, IL-10, and TGF-beta(1) levels have been correlated with aGVHD, sIL-2R levels at engraftment may provide a better parameter for early detection of aGVHD after allogeneic HSCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
1
7

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 0 publications
1
50
1
7
Order By: Relevance
“…13,14 IL-10 is a well-known suppressive cytokine of T-cell proliferation; previous studies have shown an association between elevated levels of IL-10 and reduced risk of aGVHD. 15,16 The main source of IL-10 is monocytes which in hematopoetic stem cell transplant patients are of donor's origin and hence a donor's low producer genotype would be expected to increase the risk of GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 IL-10 is a well-known suppressive cytokine of T-cell proliferation; previous studies have shown an association between elevated levels of IL-10 and reduced risk of aGVHD. 15,16 The main source of IL-10 is monocytes which in hematopoetic stem cell transplant patients are of donor's origin and hence a donor's low producer genotype would be expected to increase the risk of GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…15 Acute GVHD has traditionally thought to be a Th1 response, and thus, cytokines including IL-12 and IFN-g have been shown to have correlations with acute GVHD. 12,14,16 IL-18, which induces the production of Th1 cytokines, has been reported by two studies to correlate with acute GVHD, with evidence that IL-18 levels decrease with successful treatment. 17,18 Paradoxically, some studies have shown that cytokines with anti-inflammatory effects are associated with acute GVHD.…”
Section: Il-2mentioning
confidence: 97%
“…As significant inflammation was thought to be a major part of the initial trigger of acute GVHD, early studies focused on acute-phase reactants, such as IL-1 and IL-6, in addition to TNF-a. [11][12][13][14] A Japanese study measured C-reactive protein in a heterogeneous group of over 200 patients with analysis showing that although higher C-reactive protein levels could predict for acute GVHD, other factors including conditioning regimen intensity, infection and unrelated donors were also associated with higher levels. 15 Acute GVHD has traditionally thought to be a Th1 response, and thus, cytokines including IL-12 and IFN-g have been shown to have correlations with acute GVHD.…”
Section: Il-2mentioning
confidence: 99%
See 2 more Smart Citations